Economic growth and complementarity between stages of human capital - Ferreira, Pedro Cavalcanti (2016)
We study the impact of the different stages of human capital accumulation on the evolution of labor productivity in a model calibrated to the U.S. from 1961 to 2008. We add early childhood education to a standard continuous time life cycle economy and assume complementarity between educational stages. There are three sectors in the model: the goods sector, the early childhood sector and the formal education sector. Agents are homogenous and choose the intensity of preschool education, how long to stay in formal school, labor effort and consumption, and there are exogenous distortions to these four decisions. The model matches the data very well and closely reproduces the paths of schooling, hours worked, relative prices and GDP. We find that the reduction in distortions to early education in the period was large and made a very strong contribution to human capital accumulation. However, due to general equilibrium effects of labor market taxation, marginal modification in the incentives for early education in 2008 had a smaller impact than those for formal education. This is because the former do not decisively affect the decision to join the labor market, while the latter do. Without labor taxation, incentives for preschool are significantly stronger.